Entre diferenciação e desigualdades socioespaciais: a percepção dos moradores da Zona Sul de Poços de Caldas (MG) - da Silva, Eduardo de Araujo [UNESP]; de Paiva Francisco, Pedro Gabriel (Universidade Estadual de Montes Claros (UNIIMONTES), 2023)
The Brazilian urban spatial structure is marked by significant socio-spatial differentiations and inequalities. Spatial differences and injustices can be seen in most cities across the country, with significant inequalities in some locations, and more subtle in others. Our objective with this study was to analyze the perception of differences and inequalities in Poços de Caldas (MG), through reports from residents of the city's South Zone. To this end, the following methodological procedures were used: (i) bibliographical survey of the topic “socio-spatial differentiation and inequalities”, based on urban geography texts; (ii) bibliographic review about the (re)production of urban space in the South Zone of Poços de Caldas; (iii) fieldwork recording photographs and descriptions; (iv) semi-structured interviews with residents of the South Zone. Through the interviews, city dwellers reported that there are several factors that impact local urban life, such as: the distance between the southern urban sector and the rest of the urban fabric; the inefficiency of the public transport system; certain urban insecurity; the absence of some infrastructure; the lack of conservation of certain public spaces. In short, it was observed that the perception of the residents themselves brings extremely important elements to understand the local urban space and, in effect, the respondents perceive the socio-spatial differences and inequalities of/in the city.